The accuracy of protein models automatically built into cryo‐EM maps with ARP/wARP. Issue 2 (8th February 2021) - Chojnowski, Grzegorz; Sobolev, Egor; Heuser, Philipp; Lamzin, Victor S.
Abstract : A new module of the ARP / wARP suite for automated model building into cryo‐EM maps is presented. Abstract : Recent developments in cryogenic electron microscopy (cryo‐EM) have enabled structural studies of large macromolecular complexes at resolutions previously only attainable using macromolecular crystallography. Although a number of methods can already assist in de novo building of models into high‐resolution cryo‐EM maps, automated and reliable map interpretation remains a challenge. Presented here is a systematic study of the accuracy of models built into cryo‐EM maps using ARP / wARP . It is demonstrated that the local resolution is a good indicator of map interpretability, and for the majority of the test cases ARP / wARP correctly builds 90% of main‐chain fragments in regions where the local resolution is 4.0 Å or better. It is also demonstrated that the coordinate accuracy for models built into cryo‐EM maps is comparable to that of X‐ray crystallographic models at similar local cryo‐EM and crystallographic resolutions. The model accuracy also correlates with the refined atomic displacement parameters.